2020
DOI: 10.4028/www.scientific.net/msf.1012.256
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Potential of Adhesion to the Substrate of Masonry and Tensile in the Flexion in Mortars of Coating with Gray of the Sewage Sludge

Abstract: This work evaluates mortars using sewage sludge calcined at temperatures of 600°C and 700°C as a hydraulic binder replacing the cement. The percentages incorporated by mass to replace the Portland cement were 10%, 20% and 30%, using the 1:3:0,60 (cement: sand: factor a/c) trace. Sludge ash was characterized and tensile strength at flexion as well as tensile strength (pullout test) were evaluated. As a way of performing a comparison with conventional mortars, the same tests were carried out using reference mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Ingunza, Camarini & Costa (2018), when incorporating the sewage sludge ash (SSA), calcined at a temperature of 850°C for 3 hours, in mortar as a mineral addition, realized that the percentage of 20% is ideal for application to from a conjunctural analysis of all the parameters analyzed, corroborating even more satisfactory results when comparing the mortar without adding the SSA for axial compression tests (Figures 4 and 5). Cunha Oliveira, Chagas, Meira, Carneiro & Melo Neto (2020), evaluated the use of calcined SSA at 600°C and 700°C, incorporated in coating mortar in percentages of 10%, 20% and 30%, and evaluating the mixtures in terms of flexural strength (Figure 6), and adhesion to the masonry substrate (Table 1). The authors concluded that both temperatures contribute to the SSA becoming reactive enough to be pozzolanic, a factor directly reflected in the increase in the flexural strengths and the adhesion of mortars, with emphasis on 700°C, which produces more dehydroxylated amorphous structure, that is, more reactive, so the resistance values are higher for the temperature of 700°C.…”
Section: Sludge Aggregatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ingunza, Camarini & Costa (2018), when incorporating the sewage sludge ash (SSA), calcined at a temperature of 850°C for 3 hours, in mortar as a mineral addition, realized that the percentage of 20% is ideal for application to from a conjunctural analysis of all the parameters analyzed, corroborating even more satisfactory results when comparing the mortar without adding the SSA for axial compression tests (Figures 4 and 5). Cunha Oliveira, Chagas, Meira, Carneiro & Melo Neto (2020), evaluated the use of calcined SSA at 600°C and 700°C, incorporated in coating mortar in percentages of 10%, 20% and 30%, and evaluating the mixtures in terms of flexural strength (Figure 6), and adhesion to the masonry substrate (Table 1). The authors concluded that both temperatures contribute to the SSA becoming reactive enough to be pozzolanic, a factor directly reflected in the increase in the flexural strengths and the adhesion of mortars, with emphasis on 700°C, which produces more dehydroxylated amorphous structure, that is, more reactive, so the resistance values are higher for the temperature of 700°C.…”
Section: Sludge Aggregatesmentioning
confidence: 99%
“…Table 1 -Results of the studies concerning the adhesion resistance of the control mortar and of the additives with calcined sludge at 600°C and 700°C, both with a 1:3 formulation. Source: Cunha Oliveira, Chagas, Meira, Carneiro & Melo Neto (2020).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Verifying the presence of pozzolanic behavior in industrial by-products makes it possible to classify whether supplementary cementitious materials (SCM) are inert (filler) or reactive (pozzolan). The pozzolanic potential of a material is configured to detonate cementing properties when it reacts in the presence of calcium hydroxide (CH), which originates from the hydrated phases of Portland cement, producing low-density calcium silicate hydrated (C-S-H) (Cunha Oliveira, Chagas, Meira, Carneiro & Melo Neto, 2020;Cunha Oliveira, Meira & Lucena, 2021), similar to that produced by C3S and C2S (tricalcium and dicalcium silicates), and which increases the durability of the cement matrix in the hardened state.…”
Section: Introductionmentioning
confidence: 99%
“…Verifying the presence of pozzolanic behavior in industrial by-products makes it possible to classify whether SCM are inert (filler) or reactive (pozzolan) (Cunha Oliveira, Meira & Lucena, 2021b). The pozzolanic potential of a material is configured by detonating cementing properties when it reacts in the presence of calcium hydroxide (C-H), which originates from the hydrated phases of Portland cement, producing low-density calcium silicate hydrated (C-S-H) (Cunha Oliveira, Chagas, Meira, Carneiro & Melo Neto, 2020;Cunha Oliveira, Meira & Lucena, 2021a), similar to that produced by C3S and C2S (tricalcium and dicalcium silicates), and which increases the durability of the cement matrix in the hardened state.…”
Section: Introductionmentioning
confidence: 99%